Biochemistry laboratory: modern theory and techniques - Boyer, Rodney (Boston, Massachusetts : Prentice-Hall, 2012)
Your biochemistry lab course is an essential component in training for a career in biochemistry, molecular biology, chemistry, and related molecular life sciences such as cell biology, neurosciences, and genetics. Biochemistry Laboratory: Modern Theory and Techniques covers the theories, techniques, and methodologies practiced in the biochemistry teaching and research lab. Instead of specific experiments, it focuses on detailed descriptions of modern techniques in experimental biochemistry and discusses the theory behind such techniques in detail. An extensive range of techniques discussed includes Internet databases, chromatography, spectroscopy, and recombinant DNA techniques such as molecular cloning and PCR. The Second Edition introduces cutting-edge topics such as membrane-based chromatography, adds new exercises and problems throughout, and offers a completely updated Companion Website.
Introduction to the biochemistry/molecular biology laboratory -- Using the computer and internet for research in biochemistry -- General laboratory procedures -- Centrifugation techniques in biochemistry/molecular biology -- Purification and analysis of biomolecules by chromatography -- Characterization of proteins and nucleic acids by electrophoresis -- Spectroscopic analysis of biomolecules -- Biomolecular interactions: ligand binding and enzyme reacations -- Molecular biology I: structures and analysis of nucleic acids -- Molecular biology II: recombinant DNA, molecular cloning and enzymology -- Protein production, purification, and characterization. Appendix I. List of software programs and web sites useful for each chapter -- Appendix II. Properties of common acids and bases -- Appendix III. Properties of common buffer compounds -- Appendix IV. pKa values and pHI values of amino acids -- Appendix V. Molecular weight of some common proteins -- Appendix VI. Common abbreviations used in this text -- Appendix VII. Units of measurement -- Appendix VIII. Table of the elements -- Appendix IX. Answers to odd-numbered study problems.
Includes bibliographical references and index.
Keywords: BIOCHEMISTRY -- LABORATORY MANUALS